Exploring the utilisation and management of Sclerocarya birrea (A. Rich.) Hochst (Marula tree) in the Beitbridge district of southern Zimbabwe - Sithembelenkosini Mguni; Phibion Chiwara; Onalenna Gwate (Cogent Social Sciences)
The marula tree can play a vital role to enhance the livelihoods within marginalised communities and aid forest management efforts. This research aimed to explore the utilisation and management of the marula tree (Sclerocarya birrea) in ward 3 of Beitbridge district, Southern Zimbabwe. A representative sample of 300 randomly selected households from five villages of ward 3 were interviewed telephonically and through the WhatsApp social media platform using a semi-structured questionnaire. The study observed that 95% of the sampled households harvested and utilised marula fruits to produce several products including jam, marula wine, nuts for consumption, and soda. In addition, marula makes a significant contribution to family income at (35%) when in season compared to other livelihood options such as livestock rearing and cropping. An average of 443 kg of marula fruits were harvested per season per village and there were significant differences (p < 0.05) in quantities harvested across villages. Households involved in marula fruit trading increased by 27% in 20 years due tø an improvement in the marula tree value chain in the district. Therefore, there is a distinct possibility for overutilisation of the marula tree products, which necessitates the need for the development of effective marula forest management plans.